We rule the night - Bartlett, Claire Eliza (Little, Brown and Company, 2019)
Revna is a factory worker, manufacturing war machines for the Union of the North. Caught using illegal magic, she fears being branded a traitor and imprisoned. On the front lines, Linne defied her father, a Union general, and disguised herself as a boy to join the army. Their only reprieve from punishment: using their magic in a special women's military flight unit and undertaking deadly missions under cover of darkness. Revna and Linne can hardly stand to be in the same cockpit. They need to work together or the enemy's superior firepower will destroy them -- if they don't destroy each other first. -- adapted from jacket